The Influence of Balancing Funds and Original Regional Income on the Human Development Index and Poverty Levels in North Sumatra Province - Sembiring, Rahmat Widya; Nurlinda; Suryanto (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
This research aims to analyze the influence of Balancing Funds and Regional Original Income on the Human Development Index and Poverty Levels in North Sumatra Province. The analytical method used in this research is a quantitative method, testing the Multiple Linear Regression method and Residual Test. This research also uses secondary data in the form of panel data (pooled data), namely combining time series data (data between times) and cross sectional (data between individuals). By testing the quality of research instruments, normality tests and classical assumption tests, you will get the best research model. The variables in this research are balancing funds (DAU, DAK, DBH) and local original income as independent variables, poverty level as moderating variable and human development index (HDI) as dependent variable. The total sample is 33 Regency/City Governments from 2015 to 2019. The results of this study show that the balancing has no fund and insignificant effect on the human development index, regional original income has a positive and significant effect on the human development index. Meanwhile, the poverty level as a moderating variable weakens the influence of balancing funds and local original income on the human development index.